An enzyme-linked immunosorbent assay for the detection of IgG antibodies against Babesia equi in horses - Baldani,Cristiane Divan (2004)
A crude antigenic preparation of Babesia equi was used to develop and establish the suitability of an enzyme-linked immunosorbent assay (ELISA) for the detection of parasite carriers. Optimal dilutions of the antigen, using positive and negative reference sera, were determined by checkboard titrations. The specificity and sensitivity of the ELISA were 100 %. A total of 90 serum samples were taken from horses from the Northeast region of São Paulo State and examined for diagnosis of equine B. equi infection by ELISA. Approximately 75% (n=67) of all the horses tested were found serologically positive for B. equi. These results suggest that the ELISA described may prove to be an appropriate serological test for epidemiological studies on B. equi infections in the field and that equine piroplasmosis is a cause for serious concern in the State of São Paulo, Brazil.